Online Research for the Benefit of Polish Theoretical and Practical Catechetics - Zellma, Anna (Studia Warmińskie, 2019)
With technological advancement, the Internet has become a useful tool in various research tasks, not only in humanities and social studies but also religious studies. Therefore, the main purpose of this article is to present online research as a new method of gathering empirical data, which deserves to be recognised by Polish catechists just like the traditional research methods. A point of departure in online research is the paradigm of pastoral and theological analysis developed at the John Paul II Catholic University of Lublin. This paradigm of research ensures both efficiency and reliability of research outcomes; it allows to properly study and assess the state of affairs within a given field of study as well as to draw conclusions relevant to practical catechetics pertaining to its improvement. It requires the application of research tools typical of quantitative and qualitative research carried out in social studies. Predominantly, such tools involve questionnaire surveys distributed via email or made available on websites. Analyses of blogs, chats, and discussion forums are also important. All of these social media should be reliable and credible.